(untitled) (Research, Society and Development, 2021)
Osteoporosis is a skeletal disorder that affects bone tissue density and predisposes to pathological fractures due to increased fragility. The treatment of this condition is through the use of drugs that can induce osteonecrosis of the jaws due to their interference in osteoclastogenesis, sometimes with exposure and sequestration of this necrotic bone. Thus, the objective of this work is a case report of a 63-year-old patient, who was being treated for osteoporosis with alendronate sodium for approximately 10 years, who presented loss of dental implants due to the occurrence of osteonecrosis of the jaws, the which was discovered after attempted rehabilitation. The patient underwent removal of implants, curettage of bone sequestration and removal of friable soft tissue. After 60 days, she presented with closed and normal colored mucosa, with no exposure of bone tissue and pain. This evidences that sequestrectomy can be used to effectively treat MRONJ and shows the importance of recognizing the factors related to the development of this alteration in bone metabolism and its implications for carrying out rehabilitative therapies. However, it is imperative that professionals be aware of possible changes in the bone tissue and soft tissue covering, considering the long half-life of these drugs.